(untitled) (Research, Society and Development, 2022)
A lot is said about citizenship, but what actions are schools developing to clarify and demonstrate in practice to students how all this works? The theme chosen for this work constantly reflects the problem experienced in many Brazilian schools, where there is a lot of talk about citizenship, but often the actions developed within the school do not meet with the strengthening of the practice of being a citizen. The experience presented here was experienced in the Bilingual EETI Professor Djalma da Cunha Batista in 2017 with the objective of preparing the student for the exercise of citizenship, awakening in it through the actions developed, the awareness of ensuring the school´s public heritage, and thus contributing to the formation of a more just and balanced society, knowledgeable of their rights and duties. The methodology used in the work was qualitative, meeting the requirements of the research - participant action. The results obtained are considered favorable since it was possible to perceive some changes in the student´s habits within the school.